2020
DOI: 10.1002/cctc.201901115
|View full text |Cite
|
Sign up to set email alerts
|

Selective Deposition of Cobalt and Copper Oxides on BiVO4 Facets for Enhancement of CO2 Photocatalytic Reduction to Hydrocarbons

Abstract: The nanostructure of a semiconductor is a crucial parameter for efficient photocatalytic performance. Hereby, we have synthesized monoclinic bismuth vanadate (BiVO 4 ) crystals with controlled ratio of {010} and {110} facets. The selective deposition of CuO x and CoO x over {010} and {110} facets has been performed using photo-reduction and photo-oxidation methods, respectively. It resulted in a highly efficient charge separation of photogenerated electrons and holes and enhancement of the photocatalytic reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 49 publications
(92 reference statements)
0
14
0
Order By: Relevance
“…Additionally, the oxygen vacancy‐Zn + centre served as a trapping site for adsorption of CO 2 and H 2 O to promote charge separation, thereby achieving high catalytic activity. Furthermore, direct production from C1 products to C2 + hydrocarbons through CO 2 reduction have been studied 79–81 . C2 + products have advantages of higher energy density and economic value than C1 products.…”
Section: Value‐added Chemicals Produced By Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the oxygen vacancy‐Zn + centre served as a trapping site for adsorption of CO 2 and H 2 O to promote charge separation, thereby achieving high catalytic activity. Furthermore, direct production from C1 products to C2 + hydrocarbons through CO 2 reduction have been studied 79–81 . C2 + products have advantages of higher energy density and economic value than C1 products.…”
Section: Value‐added Chemicals Produced By Reductionmentioning
confidence: 99%
“…Furthermore, direct production from C1 products to C2 + hydrocarbons through CO 2 reduction have been studied. [79][80][81] C2 + products have advantages of higher energy density and economic value than C1 products. However, direct production of C2 + products has many thermodynamic limitations, such as C-C coupling, which is a rate-determining step.…”
Section: Co 2 Reductionmentioning
confidence: 99%
“…For example, TiO 2 has been considered as one of the most popular semiconductors applied to photocatalysis with prestigious advantages, including easy availability, low toxicity, outstanding chemical stability, and unique optical and electronic properties, and a recently published review on TiO 2 ‐based photocatalysts for CO 2 reduction is available 54 . Nevertheless, because of inefficient solar energy utilization substantiated by the wide bandgap, researchers have employed various methods to improve the activity of such photocatalysts, including metal or non‐metal doping, 40,41,55‐61 alloying, 42,51‐53 facet engineering, 62‐65 nanostructure tailoring, 13,40,46,66,67 surface defect engineering, 43,68,69 and p‐n heterojunction or Z‐scheme system constructing 44,45,47‐50,70‐74 . In general, these methods all aim at either improving the separation efficiency of photogenerated electron/hole pairs, namely prolonging the lifespan of electrons for CO 2 reduction, or creating more catalytically active sites.…”
Section: Introductionmentioning
confidence: 99%
“…Bismuth vanadate (BiVO 4 ) is an inorganic compound and well‐known semiconductor with frame structures. Many studies have shown that BiVO 4 ‐based compounds are emerging in many fields, such as reduction of carbon dioxide, water splitting, and semiconductor absorber, but BiVO 4 as a potential candidate for Li‐S batteries has not been reported so far 54‐57 …”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that BiVO 4 -based compounds are emerging in many fields, such as reduction of carbon dioxide, water splitting, and semiconductor absorber, but BiVO 4 as a potential candidate for Li-S batteries has not been reported so far. [54][55][56][57] Here, frame-structured neodymium-doped bismuth vanadate (Nd:BiVO 4 ) nanoarchitectures are reasonably designed and fabricated via a cost-efficient and facile tactics as a polysulfide shield to alleviate the shuttling effects. The crystal structure, surface topography, local structure, surface chemistry, and electrochemical properties of Nd:BiVO 4 nanoarchitectures were investigated across-the-board.…”
mentioning
confidence: 99%